1998
DOI: 10.1046/j.1365-201x.1998.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular charge selectivity for horseradish peroxidase and albumin at low and normal ionic strengths

Abstract: The classical concept of a negative glomerular charge barrier has recently been questioned, mainly based on the somewhat high clearance for anionic horseradish peroxidase (HRP). The validity of using anionic HRP can be tested by changing the properties of the charge barrier. A rather unequivocal approach is to reduce the ionic composition of the perfusate and hence increase the Debye length. We determined the glomerular clearance for horseradish peroxidase and serum albumin, using isolated rat kidneys perfused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
59
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 39 publications
(57 reference statements)
12
59
1
Order By: Relevance
“…Much of the evidence in favor of charge selectivity of the glomerular filter has been based on comparisons between sieving data for uncharged and anionic dextran (dextran sulfate) (3). Although vivid arguments against glomerular charge selectivity have been raised during the last decade (5,26,32,42), strong evidence supporting the classic view was recently given by comparing neutral and anionic lactate dehydrogenase or neutral and anionic HRP in the IPK (13,31). These studies largely confirm the classic studies by Rennke et al (22) for differently charged HRP (22).…”
Section: ϫ4supporting
confidence: 76%
“…Much of the evidence in favor of charge selectivity of the glomerular filter has been based on comparisons between sieving data for uncharged and anionic dextran (dextran sulfate) (3). Although vivid arguments against glomerular charge selectivity have been raised during the last decade (5,26,32,42), strong evidence supporting the classic view was recently given by comparing neutral and anionic lactate dehydrogenase or neutral and anionic HRP in the IPK (13,31). These studies largely confirm the classic studies by Rennke et al (22) for differently charged HRP (22).…”
Section: ϫ4supporting
confidence: 76%
“…More recently, focus has shifted to the podocytes, since several novel proteins in the podocyte slit diaphragm have been found to be important for the barrier function [1][2][3]. In addition, we have suggested a role for the glomerular endothelial cell glycocalyx [4][5][6][7][8][9][10], an idea supported also by others [11,12].…”
Section: Introductionsupporting
confidence: 72%
“…Alternatively, the tubular processes may be inhibited by toxins [24], but such drugs seem to affect permeability per se [25]. At present, one of the most reliable estimates of glomerular filtration is obtained by using the cooled isolated perfused kidney (cIPK) model, either in rats [4,8,26] or in mice [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in intact kidneys with a higher size selectivity to native proteins than in the fIPK, Lund et al (37) found a ratio of of ϳ7-10 between neutral and native (negatively charged) albumin, later confirmed by Bakoush et al (2). Similarly, high values were obtained for the ratio of the largely neutral probe LDH-5 to the negatively charged LDH-1 in the cIPK, the ratio averaging 7.59 (range 4.11-11.94) (61). On the other hand, studies comparing the clearances of neutral IgG 2 to anionic IgG 4 (pI 5.5-6.0) have yielded results indicating a lower degree of charge selectivity, with IgG 2 /IgG 4 ratios varying from 1.35 (21) and 4 (65) up to 10 (18).…”
Section: Charge Selectivity Of the Glomerular Filtration Barrier Vis-mentioning
confidence: 51%